Synthesis and Antimicrobial Activity of Quinazolinone Conjugated Peptides - G. P. Suresha; K. C. Prakasha; Wethroe Kapfo; D. Channe Gowda (E-Journal of Chemistry)
Antimicrobial compounds were synthesized by coupling 4-(4-oxo-3,4-dihydroquinazolin-2-yl) butanoic acid with VP, GVP, VGVP and GVGVP peptides. Antimicrobial activities of the synthesized compounds were performed against various bacterial strains by disc diffusion method. The structure activity relationship was evaluated with respect to hydrophobicity, polarity, chain length of peptides and alkyl chain length of quinazolinone. Correlations of analogs with respect to their antimicrobial activity in comparison with conventional drugs and probable mechanism for the activity were discussed.